Two rare mutations in homozygosity synergize to silence TREX1 in Aicardi-Goutières syndrome - Rubin, Tamar; Bernier, Stéphane; Hoon Lim, Lily Siok; Salman, Michael S.; Leung, Edward; Mhanni, Aziz; Marles, Sandra; Greenberg, Cheryl; Perez, Anna; Sun, Yichun; Angers, Isabelle; Vinh, Donald C.; et al. (Frontiers in Immunology, 2025)
BackgroundAicardi-Goutières syndrome (AGS) is a rare monogenic type I interferonopathy characterized by dysregulated inflammation and tissue damage that primarily affects the central nervous system. AGS is genetically diverse, with pathogenic variants across multiple genes, including TREX1, which drives excessive type I interferon (IFN) production.ObjectiveThis study investigated the genetic and molecular mechanisms underlying AGS in a family of two affected children, focusing on the role of TREX1 variants in protein expression and dysregulation of the interferon pathway.MethodsGenomic sequencing data were used to identify TREX1 variants in the affected children. Functional assays in patient-derived lymphoblastoid cells (LCLs) and cell line models were used to evaluate TREX1 expression and activation of the cGAS-STING pathway.ResultsTwo homozygous TREX1 variants were identified in two affected children. Functional analyses showed that both variants are required to mirror the near-absent protein levels observed in LCL and to cause excessive activation of IRF3 in cGAS-STING pathway in response to cytosolic DNA stimulation.ConclusionTo our knowledge, our findings demonstrate, for the first time, the compound effect of two rare homozygous variants account for AGS. This also reiterates the importance of molecular and functional assessments of genomic variants identified by sequencing.